Exposed Lives, Suffering and Moral Injury: The Case of Workers in the Psychosocial Area in Times of the Covid-19 Pandemic [Vidas Expuestas, Sufrimiento y Agravio Moral: El Caso de Trabajadores del Área Psicosocial en Tiempos de Pandemia Covid-19] - Calquin-Donoso, C (Pontificia Universidad Catolica de Valparaiso, 2021)
The results of a study, carried out in Santiago, Chile, are presented, which aimed to identify the work experiences of workers in the psychosocial area of the programs that make up the Chile Crece Contigo social protection system and in the context of the pandemic, taking Axel Honneth s recognition theory as a frame of reference. This is a qualitative study in which a semi-structured interview was applied to 15 professionals from eight districts of the Región Metropolitana. The results are structured in four categories: Work in the air; Lack of implementation supports: Exposed lives; Personal costs: Working without conditions, and In COVID mode: Scenario for new agencies. It is concluded that professionals have been exposed to negative forms of recognition and that could be explained by the precarious work conditions and the lack of institutional support for intervention and the new demands for assistance caused by the health crisis. It is highlighted that this precarious scenario has mobilized new labor agencies in which creativity and criticism are key. © 2021 Pontificia Universidad Catolica de Valparaiso. All rights reserved.
Keywords: Precariousness; psychosocial workers; recognition